A STUDY ON INCLUSIVE GROWTH OF EDUCATION AND EDUCATIONAL PROGRESS IN RURAL AREAS – WITH SPECIAL REFERENCE TO HASSAN - M.C, Girish; Y.D, Rathna (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Inclusive growth in education in India and Karnataka has become a focal point in recent years, aiming to ensure equitable access for all, regardless of socio-economic status, gender, or region. According to the Ministry of Education, India’s literacy rate reached 77.7% in 2021, showing steady progress, but challenges remain, particularly in rural and marginalized areas. The government’s push for Universal Elementary Education, through initiatives like the Right to Education Act (RTE), has led to higher enrolment rates, especially among girls and children from disadvantaged communities. In Karnataka, significant strides have been made to improve educational access. The state’s literacy rate stands at 77.2% as per the 2021 Census, with a noticeable increase in female literacy. Recent programs like "Vidya Vahini," which integrates technology into schools, and the "Karnataka State Higher Education Council," which promotes skill development, aim to bridge gaps in education. However, disparities still exist, particularly in remote rural areas, where students face challenges such as inadequate infrastructure and limited access to quality teachers. Government policies, such as the “Karnataka Education Policy 2020,” emphasize digital education, vocational training, and scholarships to ensure that every child, irrespective of background, receives a quality education, fostering inclusive growth for the future.